An Elective Course on Dermatological Topics and Cosmeceutical Compounding - McConaha, Jamie L. (American Journal of Pharmaceutical Education, 2014)
Objective. To implement and assess a pharmacy dermatology and cosmeceutical compounding elective course and its impact on graduates’ careers. Design. A 3-credit elective course that incorporated classroom lectures on ambulatory dermatologic diseases and cosmeceutical products with case studies, weekly quizzes, and a comprehensive business plan project was implemented in a doctor of pharmacy (PharmD) program in 2010. Assessment. Assessment instruments including weekly quizzes, a business plan project, and pre- and post-course tests were used to evaluate course content. Across 3 offerings of the course (2010, 2011, 2012), pre- and post-course test scores improved. Results of a postgraduate survey showed that 54% of respondents worked at a pharmacy offering compounding services, and 57% felt that the course played a significant or very significant role in their counseling on dermatologic conditions. Conclusions. Assessment methods revealed student learning of course content and the course appeared moderately beneficial to graduates’ early careers. A more longitudinal analysis is needed to assess the course’s impact on long-term career choices, particularly those dealing with compounding of cosmeceutical products.